MODEL INTEGRASI KEILMUAN PADA SEKOLAH MENENGAH ATAS NEGERI UNGGUL KABUPATEN ACEH TIMUR - Muhaini, Muhaini (Journal Analytica Islamica, 2019)
Abstract: The educational trend for modern society is based on science and technology to achievesuccess for the future, so the excellent schools to be a very appropriate choice, SMA Negeri UnggulKabupaten Aceh Timur is one of the excellent school. The school puts more emphasis on scientificdisciplines, the observable fact, and it can only be proved empirically. The unreal and unseen arerejected as scientific knowledge. This research aims to determine the background, model and the opportunitiesas well as challenges in the implementation of integration in SMAN Unggul Kabupaten Aceh Timur. It isa kind of qualitative research with a view to understanding the education system that runs in the school.Researcher himself became an instrument in this research. Data and information in the field becomethe main requirement in data processing.The study found that dialogical didactic was the model implementedat SMAN Unggul through the curriculum 13 approach, and the teachers were aware of the dichotomiesof the disciplines. They were able to integrate the science and the divinity into the sub-theme in theclassroom instruction. The curriculum 13 sets the main and basic competence that leads to the realizationof God, the Almighty and at the same time serves as the goal of national education. In addition, thestudy revealed the strong internalization of Islamic values in extra-curricular activities carried out throughthe traditional Islamic educational system (dayah), the commemoration of Islamic festivals, the archerysport and other activities. In short, the educational system at SMAN Unggul is a public school featuringIslamic school characteristics.Kata Kunci: Model, Integrasi dan Desain Sekolah Negeri Unggul